Bioartificial bone grafting:Tarsal joint fusion in a dog using a bioartificial composite bone graft consisting of β-tricalciumphosphate and platelet rich plasma – A case report - Hauschild, G.; Merten, H.-A.; Bader, A.; Uhr, G.; Deivick, A.; Meyer-Lindenberg, A.; Fehr, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Grafting of large bone defects caused by trauma or tumor resection still remains a problem to solve. In experimental studies as well as in human dentistry, osteoconduction and biodegradation of the β-tricalciumphosphate Cerasorb® as well as osteoinductive capabilities of platelet rich plasma have been proven. In case of luxation of the right tarsal joint, including a compressive fracture of the forth tarsal bone, the recommended use of autologous cancellous bone to support osseous fusion was replaced by the use of a bioartificial bone graft. Biodegradation of the bone graft was proven clinically and radiographically. Complete osseous fusion of the intertarsal joint occurred. The use of the β-tricalciumphosphate Cerasorb in combination with platelet rich plasma to support a partial arthrodesis of the tarsal joint in a dog did not impede the healing process but led to full recovery of the patient, indicating that this concept of bioartificial bone grafting could support bone healing.
Keywords: Bonegraft; β-tricalciumphosphate